1998
DOI: 10.1038/sj.jhh.1000692
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of vessel wall properties in normotensive and hypertensive renal transplant recipients

Abstract: The mechanisms responsible for reduced arterial distensibility in renal transplant recipients remain to be evaluated. The present longitudinal study was aimed to evaluate the effect of hypertension on the evolution of vessel wall properties in renal transplant recipients. The mechanical properties of the common carotid artery were determined in 24 normotensive and 24 treated hypertensive renal transplant recipients 6-12 weeks after transplantation. The measurements were repeated after 2 years. Arterial distens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
2
5
0
1
Order By: Relevance
“…These results showed that the impact of kidney transplantation on recipient aortic stiffness is dependent on the donor age and suggested that ongoing damage to large arteries might contribute to the mechanism underlying the association of old donor kidneys and increased cardiovascular mortality. Such findings are consistent with those indicating that reduced carotid distensibility predicts cardiovascular complications in patients after renal transplantation [9]. Taken together, all these results indicate that aortic stiffness is increased in kidney transplant recipients irrespective of whether the graft is harvested from deceased or living donors.…”
Section: See Original Paper On Page 2213supporting
confidence: 91%
See 1 more Smart Citation
“…These results showed that the impact of kidney transplantation on recipient aortic stiffness is dependent on the donor age and suggested that ongoing damage to large arteries might contribute to the mechanism underlying the association of old donor kidneys and increased cardiovascular mortality. Such findings are consistent with those indicating that reduced carotid distensibility predicts cardiovascular complications in patients after renal transplantation [9]. Taken together, all these results indicate that aortic stiffness is increased in kidney transplant recipients irrespective of whether the graft is harvested from deceased or living donors.…”
Section: See Original Paper On Page 2213supporting
confidence: 91%
“…This could suggest that analysis obtained from the 10 patients included in the cyclosporine arm may not be truly representative of what generally happens. Furthermore, it is well established that in the same subject, the affinity and binding of cyclosporine may modify the drug effect differently in the various vascular tissues [2,3,9]. Therefore, as the authors recognize, all these difficulties do not allow these results to be regarded as providing indisputable evidence for a protective effect of everolimus.…”
Section: See Original Paper On Page 2213mentioning
confidence: 74%
“…In contrast to the results in hypertensive patients with end-stage renal disease, 20,21 recent studies in essential hypertension indicate that higher distending pressure rather than structural alterations may account for arterial stiffness in essential hypertension. 22,23 The effects of sympathetic stimulation on arterial mechanical properties are complex and depend on passive effects of the increased arterial pressure and of changes in vessel geometry and smooth muscle tone due to active vasoconstriction.…”
Section: Discussionmentioning
confidence: 51%
“…4,5,[13][14][15] Clinical studies have shown that increased IMT and stiffness of the large arteries independently predict cardiovascular morbidity and mortality in adults with ESRD. 16,17 Recently, these abnormalities have been demonstrated in young adults who developed ESRD during childhood.…”
Section: Discussionmentioning
confidence: 99%